Diffusion model for the financing of a fund that risks ruin - Ferreira, Manuel Alberto M. (2013)
It is proposed initially a diffusion process to represent a system subject to systematic ruin, with a stochastic regime of inflows and outflows of capital, establishing an analogy between this process and a pensions fund. Based the system in a periodic reflection scheme, it is valued the additional necessary financing to overcome the ruin. It is used, with this propose the Renewal Theorem for “renewal-reward” processes. That valuation is discussed, when it is applicable a deterministic interest rate, after the first passage times Laplace Transform.